The Effect of Stingless Bee Nest (Heterotrigona itama Cockerell) on Anti-Predatory Behavior of Sumatran Elephant (Elephas maximus sumatranus Temminck) - Anjalia Santika; Abdullah Abdullah; Khairil Khairil; Asiah Asiah; Ismul Huda (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2022)
AbstractThe Sumatran elephant is the largest land mammal that is threatened with extinction. Elephants are threatened for their survival due to habitat loss and human-elephant conflict. One of the mitigation efforts to reduce human-elephant conflict is to use the beehive fence method. Stingless bee was thought to influence elephant behavior. In this study, the behavior of the elephants that chosen was anti-predator behavior. The purpose of this study was to determine the effect of the stingless bee nest on elephant anti-predator behavior and to find out how the elephant's anti-predator response was. This study used field experiment method and for observing elephant behavior using a focal animal sampling technique. The data obtained were analyzed using the Kruskal Wallis test. The results showed that at treatment distances P1 (1 m) and P2 (1≤X5 m) the dominant response was elephant retreating away with a percentage of 67%. The conclusion of this study is that the stingless bee nest affects the behavior of the Sumatran elephant and the form of anti-predator response shown are flicking the trunk, produce sound and retreating away from the stingless bee nest.Keywords: stingless bee, behavior, anti-predator, Sumatran elephant AbstrakGajah Sumatera merupakan mamalia darat terbesar yang terancam punah. Gajah terancam keberlangsungan hidupnya dikarenakan hilangnya habitat serta terjadinya konflik manusia-gajah. Salah satu upaya mitigasi untuk mengurangi konflik manusia-gajah ialah dengan menggunakan metode pagar sarang lebah. Kelulut diperkirakan dapat mempengaruhi perilaku gajah. Pada penelitian ini perilaku gajah yang dipilih ialah perilaku anti-predator. Tujuan penelitian ini adalah untuk mengetahui pengaruh sarang kelulut terhadap perilaku anti-predator gajah serta mengetahui bagaimana respon anti-predator gajah. Penelitian ini menggunakan metode field experiment dan untuk pengamatan perilaku gajah menggunakan teknik focal animal sampling. Data yang diperoleh dianalisis menggunakan uji Kruskal Wallis. Hasil penelitian menunjukkan bahwa pada jarak perlakuan P1 (1 m) dan P2 (1≤X5 m) respon yang mendominasi ialah gajah mundur dengan presentase 67%. Kesimpulan hasil penelitian ini adalah sarang kelulut berpengaruh terhadap perilaku Gajah Sumatera dan bentuk respon anti-predator yang ditampakkan berupa mengibaskan belalai, bersuara dan mundur menjauh dari sarang kelulut.Kata Kunci: kelulut, perilaku, anti-predator, gajah Sumatera